The Effectiveness of Flipped Classroom based Online Based Learning Model on Students Creative Thinking Skills - Mardiani, Eri; Rahmawati, Irma; Djafri, Novi; Suharto, Suharto; Agustina, Ika; Hia, eRA Era; Luciana, Occe (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to determine the effectiveness of flipped classroom-based online learning to improve students' creative thinking skills. The type of research is meta-analysis research. Research data comes from 13 national and international journals published in 2018-2023. Data analysis using the JSAP application. The inclusion criteria in this meta-analysis are research obtained from Google Scholar, Researchgate, Taylor of Francis and Mendeley, research must be experimental or quasi-experimental methods related to flipped classroom-based online learning in experimental classes and conventional models in control classes, research comes from indexed journals SINTA and Scopus and research have complete data to calculate the effect size value. The research results concluded that the implementation of online based learning based on the flipped classroom had a positive effect on students' creative thinking skills with a mean effect size value of 1.080 in the high effect size category. These findings explain that online learning based on the flipped classroom is effectively implemented by schools to encourage students' creative thinking skills.Keywords:Online Based Learning, Flipped Classroom, Effect